2022
DOI: 10.1177/0271678x221075967
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia increases blood-brain barrier permeability during extreme apnea in humans

Abstract: Voluntary asphyxia imposed by static apnea challenges blood-brain barrier (BBB) integrity in humans through transient extremes of hypertension, hypoxemia and hypercapnia. In the present study, ten ultra-elite breath-hold divers performed two maximal dry apneas preceded by normoxic normoventilation (NX: severe hypoxemia and hypercapnia) and hyperoxic hyperventilation (HX: absence of hypoxemia with exacerbating hypercapnia) with measurements obtained before and immediately after apnea. Transcerebral exchange of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…However, it remains unclear to what extent basal differences in testosterone could have influenced the findings of the present study given the controversy reported in the literature in both lowlanders (Friedl et al., 1988; Vasankari et al., 1993) and native highlanders (Garmendia et al., 1982; Gonzales et al., 2009) exposed to HA. Furthermore, we were unable to (more) directly assess BBB integrity by employing dynamic contrast‐enhanced and dynamic susceptibility contrast MRI (Tofts & Kermode, 1991) or via quantification of CSF to blood NVU proteins and/or transcerebral exchange (arterial‐to‐jugular venous concentration) gradients (Bailey, Bain et al., 2022; Lindblad et al., 2020), hence the focus on ‘surrogate’ albeit validated peripheral biomarkers (Janigro et al., 2020). Finally, it would have been of interest to assess cerebral tissue O 2 consumption/metabolism using near infra‐red spectroscopy and/or derivation of cerebral mitochondrial PO2${P_{{{\rm{O}}_{\rm{2}}}}}$ inferred from arterial and jugular venous blood gas data, given prior research documenting that local reductions in (mitochondrial) PO2${P_{{{\rm{O}}_{\rm{2}}}}}$ may serve as the upstream (potentially hormetic) signal underlying systemic/cerebral free radical formation (Bailey et al., 2011; Bailey et al., 2018; Bailey et al., 2009; Woodside et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear to what extent basal differences in testosterone could have influenced the findings of the present study given the controversy reported in the literature in both lowlanders (Friedl et al., 1988; Vasankari et al., 1993) and native highlanders (Garmendia et al., 1982; Gonzales et al., 2009) exposed to HA. Furthermore, we were unable to (more) directly assess BBB integrity by employing dynamic contrast‐enhanced and dynamic susceptibility contrast MRI (Tofts & Kermode, 1991) or via quantification of CSF to blood NVU proteins and/or transcerebral exchange (arterial‐to‐jugular venous concentration) gradients (Bailey, Bain et al., 2022; Lindblad et al., 2020), hence the focus on ‘surrogate’ albeit validated peripheral biomarkers (Janigro et al., 2020). Finally, it would have been of interest to assess cerebral tissue O 2 consumption/metabolism using near infra‐red spectroscopy and/or derivation of cerebral mitochondrial PO2${P_{{{\rm{O}}_{\rm{2}}}}}$ inferred from arterial and jugular venous blood gas data, given prior research documenting that local reductions in (mitochondrial) PO2${P_{{{\rm{O}}_{\rm{2}}}}}$ may serve as the upstream (potentially hormetic) signal underlying systemic/cerebral free radical formation (Bailey et al., 2011; Bailey et al., 2018; Bailey et al., 2009; Woodside et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This finding predicts that patients with reduced glomerular filtration rate may have elevated levels of S100B (and other biomarkers) in the absence of a BBB contribution. A recent study [ 31 ] has shown that a constant source of S100B from brain to blood exists. This is an indirect validation of our modeling effort.…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, strenuous exercise or performance in extreme sports results in BBB “opening,” possibly due to a mechanism involving free radical formation, as suggested by ref. [ 31 ]. In any case, it is not known how different sources of S100B contribute to the peripheral signal in blood (or saliva) [ 2 , 26 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is due to free radical formation. It is thus possible that the increases in S100B after strenuous exercise are due to free radical formation, BBB disruption and elevation in brain-derived S100B ( 128 ).…”
Section: Sports Biomarkers and Tbimentioning
confidence: 99%